Bibliography of Ethiopian Semitic, Cushitic, and Omotic Linguistics XXVII: 2023 - Krzyżanowska, Magdalena; Bulakh, Maria; Ghion-Hamadu, Karin (Aethiopica, 2024)
Bibliography of Ethiopian Semitic, Cushitic, and Omotic Linguistics XXVII: 2023